Characterization, complete genome sequencing, and CRISPR/Cas9 system-based decontamination of a novel Escherichia coli phage TR1 from fermentation substrates - Dong, Yuqi; Huang, Yunfei; Fan, Huahao; Song, Lihua; An, Xiaoping; Xu, Shan; Li, Mengzhe; Tong, Yigang (Frontiers in Microbiology, 2023)
Phage contamination has become a major concern for industrial bacteria, such as Escherichia coli BL21(DE3), used in fermentation processes. Herein, we report a CRISPR/Cas9 defense systembased strategy to precisely prey and degrade phage DNA to decontaminate target phages. Firstly, we isolated a novel phage from fermentation substrates with BL21(DE3) as the host, named TR1.It showed a typical podovirus morphology with a head diameter of 51.46±2.04 nm and a tail length of 9.31±2.77 nm. The burst size of phage TR1 was 151 PFU/cell, suggesting its strong fecundity in the fermentation system. Additionally, whole-genome sequencing revealed that phage TR1 has a DNA genome of 44,099 bp in length with a 43.8% GC content, encoding a total of 68 open reading frames. Comparative genomics and phylogenetic analysis designated this phage to be a new species of genus Christensenvirus. To counteract with phage TR1, we employed the CRISPR/Cas9 systembased strategy and construct two phage-resistant E. coli strains, BL21-C and BL21-T, based on conserved genes. Both EOP assays and growth curves indicated strong phage resistance of the recombinant strains, without affecting cell growth. Therefore, this work is aimed to provide a resilient strategy to response to ever-changing phages and ongoing phage-host arms race in industrial fermentation environments by personalized design of spacers in the recombinant CRISPR/Cas system-containing plasmid. More importantly, our research sparks the use of phage defense mechanism to prevent phage contamination in extensive biotechnological applications.